Measurement of the difference of time-integrated CP asymmetries in D0→K-K+ and D0→π-π+ decays - Aaij, Roel; D'Argent, Philippe; Bachmann, Sebastian; Braun, Svende; Britsch, Markward; Comerma-Montells, Albert; De Cian, Michel; Esen, Sevda; Gerick, David; Gersabeck, Evelina; Grillo, Lucia; Han, Xiaoxue; et al. (Physical review letters, 2016)
A search for CP violation in D0→K−K+ and D0→π−π+ decays is performed using pp collision data, corresponding to an integrated luminosity of 3 fb−1, collected using the LHCb detector at center-of-mass energies of 7 and 8 TeV. The flavor of the charm meson is inferred from the charge of the pion in D*+→D0π+ and D*−→¯¯¯D0π− decays. The difference between the CP asymmetries in D0→K−K+ and D0→π−π+ decays, ΔACP≡ACP(K−K+)−ACP(π−π+), is measured to be [−0.10±0.08(stat)±0.03(syst)]%. This is the most precise measurement of a time-integrated CP asymmetry in the charm sector from a single experiment.
*LHCb Collaboration: R. Aaij, P. D'Argent, S. Bachmann, S. Braun, M. Britsch, A. Comerma-Montells, M. De Cian, S. Esen, D. Gerick, E. Gersabeck, L. Grillo, X. Han, S. Hansmann-Menzemer, A. Jaeger, M. Kecke, M. Kolpin, K. Kreplin, B. Leverington, J. Marks, M. Meissner, D.S. Mitzel, S. Neubert, M. Neuner, T. Nikodem, A. Piucci, M. Stahl, U. Uwer, M. Vesterinen, A. Zhelezov [und 702 weitere Personen]
Im Titel sind die Zahl 0 und die Zeichen + und - hochgestellt
Gesehen am 10.07.2020